IDENTIFIKASI PERUBAHAN PENGGUNAAN LAHAN KOPI MENGGUNAKAN CITRA SPOT 7 DI KABUPATEN DAIRI TAHUN 2014-2022 - Hartanty Surya Ningsih; M Taufik Rahmadi; Rohani Rohani; M. Ridha Syafii Damanik; Eni Yuniastuti (Jurnal Pendidikan Geografi Undiksha, 2026)
Changes in coffee plantation land use are closely related to sustainability of production and regional land management. Dairi Regency, as one of the main coffee producing areas in North Sumatra, has shown indications of a decline in coffee land area in recent years. This study aims to identify changes in coffee land use in Dairi Regency between 2014 and 2022 and to analyze the factors influencing these changesThe research method uses a quantitative approach based on remote sensing and Geographic Information Systems (GIS) utilizing SPOT 7 satellite imagery. Land use classification is performed using the Random Forest algorithm, while change analysis is performed using an overlay technique. Accuracy testing is performed using a confusion matrix to obtain the level of classification accuracy. The results indicate a decrease in coffee plantation area accompanied by an increase in non coffee vegetation and built up areas, with an Overall Accuracy of 80 percent and a Kappa value of 0.76. The changes were influenced by climatic, social, and economic factors.